The importance of reactive agility tests in differentiating adolescent soccer players - Trajkovic, N.; Sporiš, G.; Kristicevic, T.; Madic, D. M.; Bogataj, S. (International Journal of Environmental Research and Public Health, 2020)
The ability to differentiate the elite from nonelite athletes is not clearly defined. We investigated level differences in speed, change of direction speed (CODS), and reactive agility in a group of trained adolescent soccer players. A total of 75 adolescent male soccer players (aged 14-19 years) were recruited. The players were grouped based on the level of play to elite, sub-elite, and amateur players. Players were tested for 5-, 10- and 20-m sprints, CODS, and reactive agility tests (RAT). Elite players had faster reaction movement time during RAT with live opponent stimuli (p = 0.01) compared to sub-elite and amateur players. Moreover, elite players showed a faster time during light stimuli (p = 0.01) but only compared to amateur players. The times for 5-m and 10-m sprint groups did not differ (p > 0.05). The results demonstrated that the skilled players (elite and sub-elite) performed better in reactive agility tests, speed, and COD speed compared to amateur players. Additionally, we can conclude that total and reaction time in the agility test with live opponent stimuli can be a significant factor that differentiates between adolescent soccer players considering their level